We want the light - Nupen, Christopher; Nupen, Christopher; Waxman, Franz 1906-1967
A television film by Christopher Nupen and his Allegro Films team which investigates the fruitful but complex relationship between the Jews and German music, and about survival and the place of music in the concentration camps of Nazi Germany. The title, We Want the Light!, is taken from a poem by a 12-year-old girl, Eva Pickova, written in the Theresienstadt concentration camp. Her words are also used in a setting for two choruses and orchestra by Franz Waxman, in his work The Song of Terezin
Title from resource description page (viewed Jul. 25, 2014)
Keywords: Holocaust survivors; Jews; Jews -- Germany -- Music -- History and criticism; World War, 1939-1945 -- Concentration camps -- Songs and music; Holocaust survivors -- Interviews; 1939-1945; Germany; Criticism, interpretation, etc; Documentary films; Interviews; Songs and music; Streaming videos